(untitled) (Biological Sciences - PJSIR, 2021)
Effect of Different Doses of Compost on Growth and Yield of Cotton Cotton is main cash crop of Pakistan that is also called "white gold". Majority of farmers from Punjab and Sindh cultivate it and earn high value in market to improve their livelihood. It is very important crop for cotton industry and people because, it provide raw material to industry and job to workers who serve in this sector from sowing to harvesting,ginning to weaving and selling. Cotton sector play important role in National economy as it is also a rich source of edible oil. In current scenario, growing cotton is becoming costly due to use of expensive inputs. To play part in reducing input cost of cotton present study conducted. The study aimed to evaluate efficacy of compost developed from crop refuse at zero cost. For this purpose performance of three cotton varieties MNH 886, FH 142 and IR 901 checked at five doses100 Kg, 200 Kg, 300 Kg, 400 Kg and 500 Kg of compost per acre. Results revealed that MNH 886 performed good among all three varieties on all doses followed by FH 142 and IR 901 respectively. MNH 886 performed good than all others, where maximum seed germination recorded 72.67%, plant height 138.93 cm, root length 35.43 cm, numbers of branches11.56, numbers of bolls 45.78 and yield 1840 Kg per acre on 500 Kg compost per acre recorded.However, minimum seed germination 48.56%, plant height 93.02 cm, root length 25.24 cm, numbers of branches 8.67, numbers of bolls 11.89 and yield was recorded 1042 Kg on 100 Kg compost per acre. Same trend of maximum growth at 500 Kg and minimum at 100 Kg compost observed on FH142 and IR901.